2012
DOI: 10.1186/1748-717x-7-39
|View full text |Cite
|
Sign up to set email alerts
|

DNMT (DNA methyltransferase) inhibitors radiosensitize human cancer cells by suppressing DNA repair activity

Abstract: Background Histone modifications and DNA methylation are two major factors in epigenetic phenomenon. Unlike the histone deacetylase inhibitors, which are known to exert radiosensitizing effects, there have only been a few studies thus far concerning the role of DNA methyltransferase (DNMT) inhibitors as radiosensitizers. The principal objective of this study was to evaluate the effects of DNMT inhibitors on the radiosensitivity of human cancer cell lines, and to elucidate the mechanisms relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 37 publications
8
98
0
6
Order By: Relevance
“…Epigenetic therapies targeting DNA methylation are under study and have been shown to sensitize cells to radiation. 4,[15][16][17] Treatment of cells with the DNA methyltransferase inhibitors psammaplin A or zebularine partially abrogated the G 2 phase arrest, increased apoptosis, and reduced the ability to repair DNA double strand breaks in cells exposed to 6 Gy radiation. 4 The DNA damage response is complex and involves changes to the cell cycle, activation of DNA repair pathways, and induction of apoptosis or, alternatively, senescence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epigenetic therapies targeting DNA methylation are under study and have been shown to sensitize cells to radiation. 4,[15][16][17] Treatment of cells with the DNA methyltransferase inhibitors psammaplin A or zebularine partially abrogated the G 2 phase arrest, increased apoptosis, and reduced the ability to repair DNA double strand breaks in cells exposed to 6 Gy radiation. 4 The DNA damage response is complex and involves changes to the cell cycle, activation of DNA repair pathways, and induction of apoptosis or, alternatively, senescence.…”
Section: Methodsmentioning
confidence: 99%
“…4,[15][16][17] Treatment of cells with the DNA methyltransferase inhibitors psammaplin A or zebularine partially abrogated the G 2 phase arrest, increased apoptosis, and reduced the ability to repair DNA double strand breaks in cells exposed to 6 Gy radiation. 4 The DNA damage response is complex and involves changes to the cell cycle, activation of DNA repair pathways, and induction of apoptosis or, alternatively, senescence. Although it has been previously shown that irradiation affects global changes in DNA methylation, it was not known whether these changes were enriched in pathways directly involved in the radiation response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Several proven or potential DNMTi (azacitidine, decitabine, zebularine, hydralazine, epigallocatechin gallate, and psammaplin A) caused radiosensitization in the NSCLC cell line A549. 47 …”
Section: Preclinical Combination Therapy With Dnmtimentioning
confidence: 99%
“…For example, psammaplin A, isolated from Psammaplysilla sponge, improved radiation-induced cell destruction in astrocytoma U373MG and lung cancer A549 cell lines. 67 Both DNMT3A and DNMT1 were depleted in U373MG and A549 cancer cells after treatment with either psammaplin A or zebularine. 67 Other natural products, including cyclopamine, curcumin, epigallocatechin 3-gallate, genistein, resveratrol, zerumbone, norcantharidin, and arsenic trioxide have been well reviewed for their ability to target SHH signaling.…”
mentioning
confidence: 99%